2019
DOI: 10.1016/j.ebiom.2019.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ultrasound attenuates DSS-induced colitis through the cholinergic anti-inflammatory pathway

Abstract: Background: Ulcerative Colitis (UC) is an Inflammatory Bowel Disease (IBD) characterized by uncontrolled immune response, diarrhoea, weight loss and bloody stools, where sustained remission is not currently achievable. Dextran Sulphate Sodium (DSS)-induced colitis is an animal model that closely mimics human UC. Ultrasound (US) has been shown to prevent experimental acute kidney injury through vagus nerve (VN) stimulation and activation of the cholinergic anti-inflammatory pathway (CAIP). Since IBD patients ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 72 publications
0
54
0
Order By: Relevance
“…Moreover, DSS causes spleen weight gain. [ 42 ] Additionally, colitis predisposes the colon to the development of cancer and promotes all stages of tumorigenesis. [ 43 ] Studies have revealed that the anti‐inflammatory properties of SAC may be related to its ability to decrease NF‐κB activation, thus leading to a blocked inflammatory signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DSS causes spleen weight gain. [ 42 ] Additionally, colitis predisposes the colon to the development of cancer and promotes all stages of tumorigenesis. [ 43 ] Studies have revealed that the anti‐inflammatory properties of SAC may be related to its ability to decrease NF‐κB activation, thus leading to a blocked inflammatory signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Cotero et al reported that engagement of the CAP was possible with non-invasive peripheral focused ultrasound (FUS), which resulted in lower cytokine expression and inflammation (Cotero et al, 2019). Moreover, it was reported in the same year that non-focused ultrasound targeting the entire right side of a mouse between the axilla and the hip improved mild IBD symptoms, possibly by activating the splenic nerve and the CAP (Nunes et al, 2019). Whether FUS neuromodulation of targeted peripheral ganglion or plexus provides a more efficacious use of the new technology and reduces more severe IBD models/symptomology has not been investigated.…”
Section: New Findingsmentioning
confidence: 99%
“…Weight loss was assessed relative to baseline weights. (Cotero et al, 2019), unlike previous ultrasound applications that required a transducer to be swept across an organ (Gigliotti et al, 2013) or left in place as unfocused ultrasound with a 5 cm 2 footprint (Nunes et al, 2019).…”
Section: Non-invasive Peripheral Focused Ultrasoundmentioning
confidence: 99%
“…The DSS acts as a negatively charged water-soluble sulfated polysaccharide with a highly variable molecular weight ranging from 5 to 1,400 kDa (Chassaing et al, 2014). Through the alteration in the concentration and the frequency of DSS administration, acute, chronic, and relapsing models of intestinal inflammation may be achieved (Di Martino et al, 2016;Nunes et al, 2019). Notably, a closely resembled human ulcerative colitis (UC) is regarded as the most severe murine colitis that is induced through the administration of 40 to 50 kDa DSS in drinking water (Okayasu I et al, 1990).…”
Section: Introductionmentioning
confidence: 99%